REVITALISASI ZAKAT PRODUKTIF DAN WAKAF PRODUKTIF SEBAGAI PENGENTAS KEMISKINAN - Razali, Ramadhan; Febriansyah, Sutan; Darni, Surya (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
Zakat and endowments are instruments of social economic stability. His success in improving the welfare of society has been engraved in history. Then what about the development of zakat and endowments at the present time and is there any impact of these instruments? The purpose of this study is to explain the main problems experienced in developing the two instruments. The type of this research is qualitative research with descriptive analysis techniques. For the two instruments to be optimal, the waqf body and the zakat body must have the latest innovations. So that the empowerment of zakat and waqf is optimal in following the times. Keywords: Zakat, Waqf, and Welfare Abstrak Zakat dan wakaf adalah instrument stabilitas sosial ekonomi. Keberhasilannya dalam meningkatkan kesejahteraan masyarakat telah terukir dalam sejarah. Lalu bagaimanakah dengan pengembangan zakat dan wakaf pada saat serta apakah instrument tersebut berdampak terhadap kesejahteraan masyarakat? tujuan dari penelitian ini adalah menjelaskan masalah utama yang dialami dalam perkembangan dua instrument ini. Jenis penelitian ini adalah penelitian kualitatif dengan teknik analisis deskriptif. Agar dua instrument menjadi optimal, maka badan wakaf dan badan zakat harus memiliki inovasi terbaru. Sehingga pemberdayaan zakat dan wakaf optimal dalam mengikuti perkembangan zaman. Kata kunci: Zakat, Wakaf, dan Kesejahteraan.